Conceptos fundamentales de Hinkelammert, Sánchez Vázquez y Vieira Pinto para la crítica en los estudios organizacionales (Tema Central) - Camara, Guilherme Dornelas (2025)
The objective of this article is to relate fundamental concepts of three authors of Latin American social thought, Franz Hinkelammert, Adolfo Sánchez Vázquez and Álvaro Vieira Pinto, in order to contribute to the critique of organizational studies. In common, all three have dedicated their works to the themes of emancipation, struggles against domination and oppressions and a commitment to social justice and the liberation of peoples. The theoretical framework highlights that these intellectuals propose the feasibility of communitarian human life as a criterion of praxis, which is an act of liberation because it does not belong to an isolated human being, subjected to the impositions of an organized system. As an individual has no means to change that system by his will, only those who organize themselves to fight to change the reality that oppresses them can do so. It is emphasized that the contribution to Latin American critical organizational studies is anchored in the passage from moral values to ethical achievements of those who in solidarity organize collectively to change the world in which they live.